Investigating the role of TWIST1 in medulloblastoma metastasis - Cardall, Alice (2021)
Introduction Medulloblastoma is the most common malignant paediatric brain tumour. Many patients present with metastatic disease and sadly this remains a powerful predictor for poor outcome. Metastasis is a complex multi-step process and the underlying molecular mechanisms behind medulloblastoma metastasis are poorly understood. One of the initial stages of this process involves the invasion of tumour cells through the basement membrane and into the leptomeningeal space. The transcription factor TWIST1 has been extensively studied in epithelial tumours and is considered as one of the master regulators initiating the first stage of this process. An in-depth analysis of the functional role of TWIST1 in initiating medulloblastoma metastasis remains to be explored. This project therefore aimed to assess the functional role of TWIST1 and whether it could play an essential part in driving medulloblastoma metastasis.